Critical Success Factors of Mobile Application Development Projects: A Qualitative Study - Hamza Khastar; Kamran Abdollahi (Journal of Information Technology Management)
This study seeks to identify the critical success factors of teams in the application-development project. To achieve this goal, a qualitative approach and content analysis was utilized. Semi-structured interviews with 14 developers and experts was performed for data collection. A systematic review of previous research shows that after 9 critical success factors. With the analysis interviews, the CSf's raised to 12; including user experience, strategy and project management, support and promotion, business models, planning and goal setting, financial and budgeting, marketing and customer needs, infrastructure, technical issues and design, contextual factors, teamwork and staffing. The results show that the customer experience, teamwork and contextual factors are core categories in the research paradigm model.